2021
DOI: 10.1021/acsnano.0c08135
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed Laser Confinement of Single Atomic Catalysts on Carbon Nanotube Matrix for Enhanced Oxygen Evolution Reaction

Abstract: The design of atomically dispersed single atom catalysts (SACs) must consider high metal-atom loading amount, effective confinement, and strong interactions with matrix, which can maximize their catalytic performance. Here reported is a promising method to synthesize SACs on highly conductive multiwall carbon nanotube (MWCNT) supports using pulsed laser confinement (PLC) process in liquid. Atomic cobalt (Co) and phosphorus (P) with a high loading density are homogeneously incorporated on the outer wall of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 51 publications
1
33
0
Order By: Relevance
“…It is worth noting that the C dl of MWCNTs can be ignored due to the poor capacitance. [ 25 ] Thus, the ECSA values of the senary HEA (50 ms‐P), senary HEA (50 ms‐CW), and senary HEA (1000 ms‐P) are calculated and correspond to 3817.5, 2095.0, 1067.5 cm −2 . In comparison with other reported catalysts, senary HEAs on MWCNTs possess superior ECSA value.…”
Section: Resultsmentioning
confidence: 99%
“…It is worth noting that the C dl of MWCNTs can be ignored due to the poor capacitance. [ 25 ] Thus, the ECSA values of the senary HEA (50 ms‐P), senary HEA (50 ms‐CW), and senary HEA (1000 ms‐P) are calculated and correspond to 3817.5, 2095.0, 1067.5 cm −2 . In comparison with other reported catalysts, senary HEAs on MWCNTs possess superior ECSA value.…”
Section: Resultsmentioning
confidence: 99%
“…Using an ultrafast pulsed laser confinement (PLC) process, atomic cobalt (Co) and phosphorus (P) high loading densities were uniformly anchored on the outer walls of 1D‐MWCNT to fabricate robust heteroatom‐doped Co‐SACs electrocatalysts for OER (Figure 7I). [ 126 ] Impressively, the overpotential for delivering a current density of 10 mA cm −2 (η 10 ) of Co‐P SAC MWCNT (290 mV) surpassed by far the value obtained for the benchmark RuO 2 catalyst (390 mV), which was attributed to the close electronic interactions between catalytic Co atomic sites and highly conductive MWCNTs (Figure 7J,K). This work launched a practical SAC design strategy that could benefit the future commercialization of these nanocatalysts.…”
Section: Electrocatalytic Applications Of Sacs and Aces Supported On ...mentioning
confidence: 96%
“…128 Kim and Han et al confined cobalt and/or phosphorus single atom catalysts on carbon nanotube matrices via 355 nm, 10 ns pulsed laser ablation of colloidal highly conductive multiwall carbon nanotubes in ethanol solutions of cobalt nitrate or phosphoric acid or both. 174 Laser synthesis without carbon nanotubes produced CoP nanoparticles. Oxygen evolution activity was assessed in 1 M aqueous KOH.…”
Section: Water Oxidation Electrocatalysismentioning
confidence: 99%
“…The Co single atom catalyst on carbon nanotubes showed the smallest Tafel slope, followed by the Co−P single atom catalyst and the P single atom catalyst; the carbon-free CoP material had the largest Tafel slope, indicative of slower kinetics during electrocatalytic turnover. 174 Amendola and Sartorel et al reported laser generated iron oxide nanoparticles that self-assembled on indium tin oxide electrodes by magnetophoretic deposition. 175 Pulsed laser in liquids synthesis using 1064 nm, 9 ns pulses, and an α-Fe target immersed in water produced magnetic FeO x nanoparticles with 5−30 nm size.…”
Section: Water Oxidation Electrocatalysismentioning
confidence: 99%